Réponses

2014-10-10T20:51:18+02:00
A = 7 x 8 + 9 x ( - 9 ) + 3
= 56 - 81 + 3
= - 25 + 3
= - 22

B = 7 x 8 + 9 x ( - 9 + 3 )
= 56 + 9 x ( - 6 )
= 56 - 54
= 2

C = ( 12,5 - 4 ) x ( - 5,8 - 4,2 )
= 8,5 x ( - 10 )
= - 85

D = 12,5 - 4 x ( - 5,8) - 4,2
= 12,5 + 23,2 - 4,2
= 35,7 - 4,2
= 31,5
2014-10-10T20:58:28+02:00
Calculez les expressions suivantes A = 7 x 8 + 9 x (- 9) + 3
A = 56 - 81 + 3
A = 56 + 3 - 81
A = - 22

B = 7 x 8 + 9 x (- 9 + 3)
B = 56 + 9 x - 6
B = 56 - 54
B = 2

C = (12,5 - 4) x (- 5,8 - 4,2)
C = (8,5) x (- 10)
C = - 85

D = 12,5 - 4 x (- 5,8) - 4,2
D = 12,5 + 23,20 - 4,2
D = 31,5